Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha

Wydawnictwo:Nowa Era

Rok wydania:2016

Rozłóż wielomian u na czynniki grupując jego wyrazy 4.86 gwiazdek na podstawie 7 opinii
  1. Liceum
  2. 2 Klasa
  3. Matematyka

Rozłóż wielomian u na czynniki grupując jego wyrazy

3
 Zadanie

1
 Zadanie
2
 Zadanie
3
 Zadanie
4
 Zadanie

`a)\ u(x)=x^3+5x^2+x+5=x^3+x+5x^2+5=x(x^2+1)+5(x^2+1)=#((x^2+1))^(Delta=0-4<0)(x+5)`

 

`b)\ u(x)=x^3+3x^2-x-3=x^3-x+3x^2-3=x(x^2-1)+3(x^2-1)=(x^2-1)(x+3)=(x-1)(x+1)(x+3)`

 

`c)\ u(x)=4x^3+x^2-16x-4=4x^3-16x+x^2-4=4x(x^2-4)+1*(x^2-4)=(x^2-4)(4x+1)=(x-2)(x+2)(4x+1)`

 

`d)\ u(x)=x^4+3x^3+x^2+3x=x^4+x^2+3x^3+3x=x^2(x^2+1)+3x(x^2+1)=#((x^2+1))^(Delta=0-4<0)(x^2+3x)=(x^2+1)(x+3)x`

 

`e)\ u(x)=x^3+4x^2-25x-100=x^2(x+4)-25(x+4)=(x+4)(x^2-25)=(x+4)(x-5)(x+5)`

 

`f)\ u(x)=sqrt5x^3-x^2-sqrt5x+1=sqrt5x^3-sqrt5x-x^2+1=sqrt5x(x^2-1)-1(x^2-1)=(x^2-1)(sqrt5x-1)=(x-1)(x+1)(sqrt5x-1)`

 

`g)\ u(x)=8x^5+16x^3-x^2-2=8x^3(x^2+2)-1(x^2+2)=(8x^3-1)#((x^2+2))^(Delta=0-8<0)=(2x-1)#((4x^2+2x+1))^(Delta=4-16<0)(x^2+2)`

 

`h)\ u(x)=x^3-sqrt2x^2+sqrt3x-sqrt6=x^2(x-sqrt2)+sqrt3(x-sqrt2)=(x-sqrt2)#((x^2+sqrt3))^(Delta=0-4sqrt3<0)`